Critical thinking at the hands of literature, cinema and video - Martins, Cláudia (2018)
Learning is considered a fundamental skill for human development, without which no evolution is even conceivable. However, formal education from 18th century onwards was gradually transferred to states’ hands and thus standardised schooling came to be. Despite enabling less privileged people to have access to culture at that time, it is a means to kill creativity and create a gap between those who follow academic pathways and those who don’t, from Ken Robinson’s viewpoint. However, education should also consist of a means to discovery, to exercise critical attitudes towards life and become the springboard for social changes. The concept of critical thinking is profusely discussed, although it exists for over 2500 years, according to the Critical Thinking Community. It is understood as a process that requires discipline and active engagement in analysing events and information, evaluating and reflecting upon them. We believe such events and information can be provided by literature, cinema and video, which we have extensively used in educational contexts at higher education with a view to developing students’ critical thinking. Literature may appear as the starting point (or not) – Henry David Thoreau’s “Walden” or “Invictus” by William Ernest Henley – complemented by classics in cinema, such as “Dead Poets Society” (Peter Weir, 1989) or “Invictus” (Clint Eastwood, 2009). A third part in this equation is played by “Ted: ideas worth spreading”, where short talks can be accessed. Therefore, the aim of this paper is to explore the power of this triad in enhancing critical thinking in young adults.